2015
DOI: 10.1007/s12540-015-4627-z
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and creep deformation of a newly developed Ni-Fe-based superalloy for 700 °C advanced ultra-supercritical boiler applications

Abstract: A new Ni-Fe-based superalloy, HT-X, has been developed for applications in 700°C advanced ultra-supercritical (A-USC) boilers. The HT-X alloy is subjected to various heat treatments. Tensile tests are conducted at room temperature (RT), 700°C and 750°C. Creep tests are carried out under conditions of 700°C/300 MPa and 750°C/150 MPa. After aging treatment, the yield strength of the HT-X alloy at RT and 750°C is 787 MPa and 624 MPa, respectively. When additional thermal exposure at 750°C for 5400 h is applied, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…However, it has poor oxidation and mechanical properties compared to intermetallic compounds [4][5][6]. As a result, Mo alloys, composed of an Mo phase and Mo-Si intermetallic compounds phases such as MoSi 3 and Mo 5 Si 3 , have been stud-ied with the aim of improving their mechanical properties and oxidation resistance [7][8][9]. However, despite the improvement of the mechanical or oxidation properties of Mo alloys, machining this alloy is difficult because of poor ductility of the alloys at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has poor oxidation and mechanical properties compared to intermetallic compounds [4][5][6]. As a result, Mo alloys, composed of an Mo phase and Mo-Si intermetallic compounds phases such as MoSi 3 and Mo 5 Si 3 , have been stud-ied with the aim of improving their mechanical properties and oxidation resistance [7][8][9]. However, despite the improvement of the mechanical or oxidation properties of Mo alloys, machining this alloy is difficult because of poor ductility of the alloys at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that steam temperatures up to 750 • C are Energies 2016, 9, 779 3 of 14 allowable in service. Yuan et al [20] analyzed the tensile and creep deformation for a newly-developed Ni-Fe-based superalloy. They found that the new material can endure 750 • C for 5400 h.…”
Section: Introductionmentioning
confidence: 99%